Gene Action, Heterosis and Combining Ability in Maize Hybrids B- Using Line x Tester Analysis - Mohammed Ali Hussain; Khalid Mohamad Dawod; Abbas Alo Khether (Kufa Journal for Agricultural Sciences)
A line x tester cross comprising eight pure lines, ZP–505, IK58, and HS, used as testers (female parents), DK-17, ZP- 430, ZP-595, UN44052, and POL-158, used as lines (male parents), was studied for nine traits (number of days to silking, number of days to tasseling, plant height, ear height, leaf area, number of rows per ear, number of grains per row, 300 grains weight and grain yield per plant, to determine the nature of gene action in parents and hybrids and estimation of heterosis. The results revealed that the mean square for genotypes, parents, and hybrids was highly were significant for all tray   whichthat is an indication of the diversity between parents (lines and testers) causes cause significant differences between single crosses among them. Also, it was shown that mean square due to each of lines and testers was highly significant for all traits indicated the presence of additive gene effects controlling these characters, and that due to the interaction of line x tester was significant at 1% level for all traits meaning the presence of dominance gene effects controlling them. The ratio of general combining ability components to the specific combining ability components was less than one for all traitsindicatingd that dominance gene effects were more prominent for all studied traits. The tester ZP–505 and line ZP-595 were the best general combiner for largest number of traits including grain yield per plant, and the crosses (HSxDK-17), (IK58xUN44052), (HSxPOL158) and (ZP–505xZP-595) showing significant specific combining ability effects and heterosis for largest number of traits and could be utilized for developing high yielding hybrid varieties as well as for exploiting heterosis. The range of narrow sense heritability ranged from 20.98% for 300GW to 55.71% for GYP, as it was high for LA (50.68%) and GYP (55.71%), and moderate for other traits.